Teacher’s Strategy in Familiarizing Children to Speak Good Words in Early Childhood - Deska Luma, Aprita; Wirman, Asdi (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2022)
Purpose – An attractive teacher’s strategy for getting children to speak kind words to friends, teachers and parents. TK Harapan Bunda Parak Laweh, children are accustomed to speaking kind words from an early age, so, in the future, children will get used to speaking kind words to the people around them. This research aims to describe teachers’ strategies, such as approaches and methods in getting children to speak words. good at TK Harapan Bunda Parak Laweh Padang.Design/methods/approach – This study uses a qualitative approach. This method uses descriptive qualitative. The informants of this study were the principal and teacher of TK Harapan Bunda Parak Laweh Padang. Data collection techniques, namely observation, interviews, and documentation. Data analysis techniques were carried out by collecting, reducing, presenting, and drawing conclusions. The data validation technique is a triangulation technique.Findings – The research results show that the teacher accustoms children to speaking good words by making the teacher a role model, and rules with children behaving at school, giving advice and punishment if children speak bad words. While the approach used by the teacher to instill a good speech attitude is to apply child-centered learning, the teacher gives the child space for children to think and explore, the teacher serves as a companion or facilitator for the child when the child makes a mistake in behaving and speaking, the teacher immediately scolds and gives directions to the child. So, it can be concluded that the strategy used by the teacher is the strategy of implementing role models. The teacher is an example for children and takes approaches and methods to accustom children to speaking well, such as telling stories and conversing and implementing learning strategies with student center learning methods where learning is child-centered.Research implications/limitations – This research only focuses on teachers’ strategies to get children to speak good words at Harapan Bunda Parak Laweh Padang.Practical implications – This research contributes knowledge and provides teachers with examples of strategies for getting children to speak well.Originality/value – Research can be used to find out the strategies used by teachers to familiarize children with good speech.Paper type: Research paper